PENGARUH MEDIA MASSA TERHADAP TAHAP PERKEMBANGAN PSIKOLOGI AGAMA PADA MANUSIA - Harsananda, Hari; Saitya, Ida Bagus Subrahmaniam (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2021)
The presence of mass media in the current era of globalization is nothing special, various kinds of media appear, grow and develop like mushrooms in the rainy season, especially with the internet that allows connections between individuals in this world. The media enter into people's lives and have an influence on one's beliefs, this is in line with the opinion of Jhon Vivian who said that mass media is a facility that carries messages to the public. A person's religious behavior arises because of an internal urge, which then gets an influence from the environment. In subsequent developments, religious behavior is much influenced by factors of religious experience, personality, psychological elements and others. Human life experiences several phases in the level of development of the religious soul in itself, including the children's phase, the adolescent phase, the adult phase, and the advanced phase. Each phase has its own characteristics and uniqueness. One of the formers of religious character in these phases is the mass media. Mass media in the present era is not only a complement but also a part of life. This media has both positive and negative influences on humans.